Graphic Imprints The Influence of Representation and Ideation Tools in Architecture - Marcos, Carlos L. (Springer International Publishing : Imprint: Springer, 2019)
This is the Proceedings of the International Congress of Graphic Design in Architecture, EGA 2018, held in Alicante, Spain, May 30-June 1, 2018. About 200 professionals and researchers from 18 different countries attended the Congress. This book will be of interest to researchers in the field of architecture and Engineering. Topics discussed are Innovations in Architecture, graphic design and architecture, history and heritage among others.